MANAJEMEN TENAGA KERJA PANEN KELAPA SAWIT DI KEBUN REDANG SEKO PT.TUNGGAL PERKASA PLANTATIONS KABUPATEN INDRAGIRI HULU - Rita Aprilia Sari; Syaiful Hadi; Evy Maharani (Fakultas Pertanian, Universitas Riau, 2017)
The weakness in oil palm plantations in Indonesia is the plantation management and the control of plant pests and diseases and one of the concerns is employment aspect. Harvest labour have a very important role in supporting the company’s production. PT. Tunggal Perkasa Plantation Company engaged in the palm oil industry. One of its palm oil plantation namely Redang Seko Gardens SR6 consists of 185 labour worker. This research aimed to determine the labour management; and to know the gap between the target and realization of harvest labour. The research was carried out at Redang Seko PT. Tunggal Perkasa Plantations, regency of Indragiri Hulu, Riau. Research was conducted from December 2015 to January 2017. The sample in the research were 30 harvest labour by using proportional stratified random sampling. The results showed that the harvest labour management has been implemented, although there are still many weaknesses in each management functions. The errors that occured due the harvest labour not suitable with the specified SOP. Based on the gap between the target and the realization with only 11 workers achieved the target, while 19 harvets workers did not achieve the target well which was caused by internal and external factors. The independent sample t test showed that the target was higher than the realization, however the result of analysis was not significant.